2017
DOI: 10.3389/fmicb.2016.02138
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Clostridium difficile PCR Ribotype 014 Lineage in Australian Pigs and Humans Reveals a Diverse Genetic Repertoire and Signatures of Long-Range Interspecies Transmission

Abstract: Clostridium difficile PCR ribotype (RT) 014 is well-established in both human and porcine populations in Australia, raising the possibility that C. difficile infection (CDI) may have a zoonotic or foodborne etiology. Here, whole genome sequencing and high-resolution core genome phylogenetics were performed on a contemporaneous collection of 40 Australian RT014 isolates of human and porcine origin. Phylogenies based on MLST (7 loci, STs 2, 13, and 49) and core orthologous genes (1260 loci) showed clustering of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
161
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(173 citation statements)
references
References 125 publications
10
161
0
2
Order By: Relevance
“…(, ), and for strain RT014, evidence was found for zoonotic transmission between pigs and humans (Knight et al . ). This transmission potential between animals and humans leads to a zoonotic risk, not only between humans and farm animals, but also pets and humans, and (indirectly) rodents and humans.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(, ), and for strain RT014, evidence was found for zoonotic transmission between pigs and humans (Knight et al . ). This transmission potential between animals and humans leads to a zoonotic risk, not only between humans and farm animals, but also pets and humans, and (indirectly) rodents and humans.…”
Section: Resultsmentioning
confidence: 97%
“…Evidence for zoonotic transmission of C. difficile (strain RT078) has only recently been reported by Knetsch et al (2014Knetsch et al ( , 2018, and for strain RT014, evidence was found for zoonotic transmission between pigs and humans (Knight et al 2017). This transmission potential between animals and humans leads to a zoonotic risk, not only between humans and farm animals, but also pets and humans, and (indirectly) rodents and humans.…”
Section: Resultsmentioning
confidence: 99%
“…The zoonotic transmission is supported by the occurrence of C. difficile in animals, and the shared PCR ribotypes between humans and animals. A more precise wholegenome analysis has confirmed an overlap of genetically related strains between humans and animals [12][13][14][15].…”
Section: Introductionmentioning
confidence: 92%
“…80 The 014 ribotype is highly prevalent in neonatal pigs in Australia, and, notably, it is the most frequent ribotype associated with CDI. 81 Analogous to the 078 ribotype, whole genome analyses of 014 strains indicates that many strains isolated from humans are genetically identical to those isolated from pigs despite being separated by large distances. 81 C. difficile is also frequently found in approximately 50% of <7-day-old calves despite being present in only 2% of adult cattle, 82 so young cows may be another important source of C. difficile spores.…”
Section: Difficile Can Be Transmitted Between Animals and Humans Bmentioning
confidence: 99%